House of open wounds - Tchaikovsky, Adrian, 1972- (Tchaikovsky, Adrian, 1972-. Tyrant philosophers, 2023)
"City-by-city, kingdom-by-kingdom, the Palleseen have sworn to bring Perfection and Correctness to an imperfect world. As their legions scour the world of superstition with the bright flame of reason, so they deliver a mountain of ragged, holed and scorched flesh to the field hospital tents just behind the front line. Which is where Yasnic, one-time priest, healer and rebel, finds himself. Reprieved from the gallows and sent to war clutching a box of orphan Gods, he has been sequestered to a particularity unorthodox medical unit. Led by 'the Butcher', an ogre of a man who's a dab hand with a bone-saw and an alchemical tincture, the unit's motley crew of conscripts, healers and orderlies are no strangers to the horrors of war. Theirs is an unspeakable trade: elbow-deep in gore they have a first-hand view of the suffering caused by flesh-rending monsters, arcane magical weaponry and embittered enemy soldiers. Entrusted - for now - with saving lives deemed otherwise un-saveable, the field hospital's crew face a precarious existence. Their work with unapproved magic, necromancy, demonology and Yasnic's thoroughly illicit Gods could lead to the unit being disbanded, arrested or worse. Beset by enemies within and without, the last thing anyone needs is a miracle..."--Amazon.